1979
DOI: 10.1055/s-0028-1092717
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentration of Antidiuretic Hormone in Patients with Chronic Renal Insufficiency on Maintenance Dialysis

Abstract: Radioimmunoassay of plasma arginine-vasopressin (AVP) in regularly dialyzed patients with chronic renal insufficiency revealed a parallel increase of AVP and plasma osmolality (POsm) before dialysis (4.16 +/- 0.36 pg/ml and 312.6 +/- 1.80 mOsm/1) and their parallel declin to the normal range (1.93 +/- 0.27 pg/ml and 292.0 +/- 1.27 mOsm/1) during dialysis. Plasma AVP correlated with POsm before and after dialysis (r = 0.611 and 0.453, p less than 0.01 and less than 0.05 respectively). The increase of AVP before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
4
10
0
Order By: Relevance
“…Our results indicating the lack of correlation of AVP versus osmolality and AVP versus mean blood pressure were in agreement with those of Shimamito et al [10], Vaziri et al [12] and Pastoriza-Munoz et al [8], but dis agreed with those of Horky et al [11], who found a weak but positive correlation between blood pressure versus AVP before dialysis only and serum osmolality versus AVP for both before and after dialysis. Variability in salt and fluid intake, type of instruments, dialysing mem brane and dialysate may contribute to these differences.…”
Section: Discussionsupporting
confidence: 82%
“…Our results indicating the lack of correlation of AVP versus osmolality and AVP versus mean blood pressure were in agreement with those of Shimamito et al [10], Vaziri et al [12] and Pastoriza-Munoz et al [8], but dis agreed with those of Horky et al [11], who found a weak but positive correlation between blood pressure versus AVP before dialysis only and serum osmolality versus AVP for both before and after dialysis. Variability in salt and fluid intake, type of instruments, dialysing mem brane and dialysate may contribute to these differences.…”
Section: Discussionsupporting
confidence: 82%
“…Twenty-six of these studies, comprising 496 patients, were eligible for the meta-analysis since these studies reported the mean and standard deviation of plasma AVP levels before and after standard HD. Several studies observed a significant increase in plasma AVP levels during HD [15,16,29,38,52,53,57], whereas the other studies did not [32,33,34,35,36,37,39,40,41,42,43,44,46,49,50,51,54,55,56,58]. Overall, plasma AVP levels showed little or no increase during standard HD (7.0 ± 4.9 and 8.8 ± 9.3 pg/ml for pre- and post-HD, respectively; p = 0.433) .…”
Section: Effect Of Dialysis On Plasma Avp Levelsmentioning
confidence: 88%
“…Other stimuli for the release of AVP during HD include nausea and pain related to puncture of the fistula. The effect of conventional HD on plasma osmolality is not well delineated, with some studies reporting no change [29,34] and others reporting a decrease in plasma osmolality [15,35,36,37,38,39,40,41,42,43,44]. Table 1 summarizes the theoretical effects of HD on AVP release.…”
Section: Stimuli For Avp Release During Hdmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that in patients undergoing hemodialysis, plasma A DH levels were significantly increased [6,15]. Elevation of plasma neuro physin in patients with CRF has also been observed [1,2,7,13].…”
Section: Introductionmentioning
confidence: 99%